Aggressive Colorectal Cancer in the Young - Read, Blake; Sylla, Patricia (Clinics in Colon and Rectal Surgery, 2020)
Despite the steady decline in the incidence of colorectal cancer (CRC) and cancer-related mortality in Americans of 50 years and older over the last few decades, there has been a disturbing trend of steadily rising incidence in early-onset colorectal cancer (EOCRC), defined as CRC in those younger than 50 years. With the incidence of EOCRC increasing from 4.8 per 100,000 in 1988 to 8.0 per 100,000 in 2015, and with the decreased rates in those older than 50 years largely attributed to improved screening in the older population, new screening recommendations have recently lowered the age for screening average-risk individuals from 50 to 45. EOCRC has been found to present differently from late-onset CRC, with a higher proportion of patients presenting with left-sided and rectal cancer, more aggressive histological features, and more advanced stage at the time of diagnosis. This article reviews the most recent evidence from population-based studies and institutional series, as well as the newest screening guidelines, and provides an up-to-date summary of our current understanding of EOCRC, from clinical presentation to tumor biology and prognosis, and future directions in treatment and prevention.
Keywords: colorectal cancer; young onset; increasing incidence